Impact of Demographic Changes on Inflation and the Macroeconomy - Yoon, Jong-Won (IMF Working Papers; Working Paper ;, 2014)
The ongoing demographic changes will bring about a substantial shift in the size and the age composition of the population, which will have significant impact on the global economy. Despite potentially grave consequences, demographic changes usually do not take center stage in many macroeconomic policy discussions or debates. This paper illustrates how demographic variables move over time and analyzes how they influence macroeconomic variables such as economic growth, inflation, savings and investment, and fiscal balances, from an empirical perspective. Based on empirical findings-particularly regarding inflation-we discuss their implications on macroeconomic policies, including monetary policy. We also highlight the need to consider the interactions between population dynamics and macroeconomic variables in macroeconomic policy decisions.